“I Don’t Want Your Compassion!”. The Importance of Empathy for Morality. - Manuel Camassa (Humana.Mente: Journal of Philosophical Studies, 2019)
After the great enthusiasm about the moral potentialities of empathy of the last thirty years, this phenomenon has been recently called into question, if not openly criticized, by both philosophers and psychologists among whom we find Jesse Prinz or Paul Bloom. This paper aims to show why empathy should not too easily be regarded as useless or even deleterious for morality and to propose a special role for it. In order to reach this goal, I will briefly sketch what I mean with the term empathy and how is this psychological mechanism different from other akin phenomena like compassion. I will then turn my attention to some criticisms that can be made about the role of empathy for morality which show that empathy seems not a necessary element of the three main dimensions of morality, that is moral judgment, moral development and moral conduct. After that, I will try to defend empathy thanks to the identification of some important roles it can play both at a moral and at an epistemological level, in the attempt to demonstrate that empathy is in fact part of the fundamental features of a moral person.